Local Wisdom in the History of Traditional Headbans Palembang South Sumatra - Muhamad Idris; Sukardi Sukardi; Riki Andi Saputro (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The cover and headband is a testament to the intelligence, perseverance, and skills of the people of South Sumatra. Cultural elements of covering and headbands in real life have various functions that are in accordance with the messages of cultural values. The purpose of this research is to carry out research or study of museum collections in an effort to provide information about the preservation and preservation of objects of historical and cultural value. The literature study method is a technique of collecting data through various literature, such as books, magazines, journals, articles, papers related to the cover and headband of South Sumatran men as well as other supporting data, such as photo and historical documentation related to the field of study. The results of the research based on the function of the museum then the preservation of the museum collection becomes the duty and responsibility of the museum manager. Preservation of the Covering and Headband of men's Headband collection of the State Museum of South Sumatra, in general, can be classified into three, namely: 1) Protection; 2) Development; and 3) Utilization.